Learning From Covid-19: Social Infrastructure in Disadvantaged Housing Areas in Denmark - Marie Stender; Lene Wiell Nordberg (Urban Planning, 2022)
The Danish post-war housing areas originally epitomised the dawn of the welfare state, with modern housing blocks organised as enclaves surrounded by open green spaces, promoting ideals like hygiene, light, fresh air, equity, and community. Often, these housing areas were developed in vacant lots in suburban areas, and social infrastructure planning was an essential part of stimulating the sense of community with centrally located community centres and other common facilities. Due to segregation, some of these housing areas have become disadvantaged neighbourhoods, and the Danish state has recently introduced new measures, including demolitions and evictions, to transform the areas and increase their social and functional mix. The social infrastructure of these areas has traditionally been a physical framework for organised social activities and social support for socially disadvantaged citizens, facilitated by professionals. However, during the pandemic lockdown, shared physical facilities were temporarily closed and all organised social activities cancelled, thus rendering visible critical aspects of social infrastructure that may normally be taken for granted or remain unnoticed. Yet the pandemic also activated communities in new ways, making visible more informal and ad hoc social infrastructure with new communication channels, practical help among neighbours, and community singing from balconies. Based on recent architectural-anthropological field studies in a range of disadvantaged housing areas in Denmark, this article locates social infrastructure during the time of Covid-19. It discusses the potential of mapping existing social networks and suggests a more differentiated view through three levels of social infrastructure learning from the pandemic’s emergency period.